Ecuaciones racionales 3204

Resuelve la ecuación \frac{3x-1}{x+2} + \frac{x}{x-2} = -\frac{1}{5}

SOLUCIÓN

\frac{3x-1}{x+2} + \frac{x}{x-2} = -\frac{1}{5}
m.c.m. : (x+2)(x-2)5

\frac{(x-2) \cdot 5 \cdot (3x-1)}{(x+2)(x-2)5} + \frac{(x+2) \cdot 5 \cdot x}{(x+2)(x-2)5} = -\frac{(x+2) \cdot (x-2)}{(x+2)(x-2)5}

(x-2) \cdot 5 \cdot (3x-1) + (x+2) \cdot 5 \cdot x = -(x+2) \cdot (x-2)
(5x-10) \cdot (3x-1) + (x+2) \cdot 5x = -(x+2) \cdot (x-2)
15x^2-5x-30x+10 +5x^2+10x = -(x^2-4)
15x^2-5x-30x+10 +5x^2+10x = -x^2+4
15x^2-5x-30x+10 +5x^2+10x +x^2-4=0
21x^2-25x+6=0
Resolvemos la ecuación de segundo grado y obtenemos como soluciones:
\fbox{x=1/3} y \fbox{x=6/7}